[Medical treatment of rheumatoid arthritis in 2014 : Current data from the German Collaborative Arthritis Centers] - Albrecht, K.; Huscher, D.; Eidner, T.; Kleinert, S.; Spathling-Mestekemper, S.; Bischoff, S.; Zink, A. (Z Rheumatol, 2017)
BACKGROUND: Since the introduction of biologic treatment in rheumatoid arthritis (RA), disease activity and treatment modalities have changed substantially. The current provision and developments in recent years are analyzed with annual data from the National Database of the Collaborative Arthritis Centers in Germany. METHODS: To analyze disease activity, diagnostics and treatment in RA patients in 2014 with regard to seropositivity and disease duration. Time trends from 2007-2014 are reported for disease activity (DAS28) distribution and biologic treatment. RESULTS: In 2014, a total of 8,084 RA patients were analyzed: 72 % were rheumatoid factor and/or ACPA positive, the mean age was 62 years and the mean disease duration 12 years. According to DAS28, 35.9 % were in remission, 19.2 % had low, 37.1 % moderate and 7.8 % high disease activity. An increase since 2007 was only observed in patients with a disease duration >2 years. Synthetic DMARDS were used for treatment in 78 %. Biologic treatment increased from 16 % (2007) to 27 % (2014). Especially those patients with a disease duration >5 years were treated more frequently with biologics. Seronegative patients had slightly less severe mean disease activity parameters. They were treated equally frequent with DMARDS but only half as often with biologics compared to seropositive patients. CONCLUSION: The use of biologics in RA patients has increased since 2007; however this was not observed in patients with short disease duration. Early intensive treatment adaption seems justified to improve disease activity in the large portion of patients who do not reach low disease activity under conventional DMARDs.